William Dawes Scientist, Governor, Abolitionist: Caught Between Science and Religion - de Grijs, Richard; Jacob, Andrew (Cham : Springer International Publishing : Imprint: Springer, 2023)
This book describes William Dawes' life and professional achievements. William Dawes was a British Marine serving as the official astronomer on board the First Fleet making the 1787-1788 voyage from Britain to the new colony of New South Wales. Between 1788 and 1791, Dawes established not one but two observatories within a kilometre of Sydney's present-day city centre, a full seven decades before the construction of Sydney's historical Observatory at Dawes' Point, today a stone's throw from the Sydney Harbour Bridge. In this comprehensive biography, the authors discuss William Dawes' life and his considerable impact-as astronomer, engineer, surveyor, ordnance officer and intellectual centre point-on the early colony in New South Wales (in essence, his impact on the earliest history of Sydney as a settlement) and, subsequently, on the British colonies of Sierra Leone on the West African coast and Antigua in the West Indies. Dawes' life and professional achievements are closely linked to the earliest history of Sydney as a British settlement. He is often considered a man of high morals, and as such his interactions with the local populations in New South Wales, Sierra Leone and Antigua were mostly deemed respectful and above reproach. He is seen a truly enlightened individual, far ahead of his time. The authors of this book have a significant track record of successful and engaging communication of complex concepts in physics and astronomy with experts and non-experts alike. This biography touches on numerous aspects related to 18th century maritime navigation ("sailing on the stars"), societal relationships, the exploration of newly discovered lands, as well as the early history of Sydney and New South Wales, and the colonial histories of Sierra Leone and the West Indies. As such, this book will appeal to a wide range of readers, from scholars in the history of science and maritime navigation, to history enthusiasts ranging from local historians on Australia's eastern seaboard to members of the public with a keen interest in British colonial history.
Part 1: 1762 (b.)-1787 -- William Dawes' Rise as a Promising Scientist -- Correspondence with the Board of Longitude -- Astronomical observations on the First Fleet from England to Australia -- Part 2: 1788-1791 -- Arrival in New South Wales, Establishment of Dawes' Observatory -- Lapérouse Expedition: Dawes-Dagelet Correspondence.-Patyegarang/Gadigal-Eora Indigenous Language Pursuits -- Military Events, Altercation with Governor Arthur Phillip -- Exploration and mapping of the colony of New South Wales -- Part 3:1792-1836 (d.) -- Sierra Leone. Abolition of Slavery Campaign -- Later Life.
Keywords: Physics -- History; Australasia; History; Astronomy -- Observations; History of Physics and Astronomy; Australian History; Astronomy, Observations and Techniques